Travelogues of the early twentieth century and Qaraqorum - Honichud, Geriletu (Acta Mongolica, 2022)
In the twentieth century, a large number of scientific research campaigns were organized in Asia, including China and Mongolia, by various countries, such as Britain, France, Germany, Russia, and Japan. Western tourists or scientists who travelled to Mongolia during the 20th century and wrote reports can be divided, in the framework of this paper, into two groups: Russian tourists and scientists on the one hand, and members of the Sino- Swedish expedition campaign on the other. Among these travellers and scholars of Mongolia were Nikolay Przhevalsky (1839-1888), Pyotr Kozlov (1863-1935) led by Sven Hedin (1865- 1952), and Haslund-Christensen (1896-1948). The travel notes left by these people cover almost the whole of Mongolia, and now these travel notes are included in Mongolian local research and used as material for the country’s history and politics, while details about farming, religion, rites, and rituals will play an important role in future research. This is especially true for the Sino-Swedish expedition as numerous travel diaries from the Sino-Swedish joint field trip to Northwest China have been published, detailing the lives of the inhabitants of Inner Mongolia as well as Xinjiang. One interesting difference among the travellers mentioned above is that some of them visited Qaraqorum while others did not. The paper will investigate the reasons for these different itineraries, as well as some of the information provided by these travellers about Mongolia.